Biosensors and environmental health - Preedy, Victor R.; Patel, Vinood B. (CRC Press, 2012)
Discussing the role biosensors play in detecting and monitoring environmental substances, Biosensors and Environmental Health provides key facts that can be applied to other areas of health and disease and a "mini-dictionary" of key terms and summary points. It covers personal toxicity testing, soil and risk assessment, pesticide, insecticides, parasites, nitrate, endocrine disruptors, heavy metals, food contamination, whole cell bioreporters, bacterial biosensors, antibody-based biosensors, enzymatic, amperometric and electrochemical aspects, quorum sensing, DNA-biosensors, cantilever biosensors, bioluminescence and other methods and applications. The contributors are leading authorities and the book is essential reading for environmental scientists, toxicologists, medical doctors, health care professionals, pathologists, biologists, biochemists, chemists and physicists, general practitioners as well as those interested in disease and sciences in general.